2009
DOI: 10.1007/s11270-009-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Aspects of Cadmium and Nickel Toxicity in the Lichens Peltigera rufescens and Cladina arbuscula Subsp. mitis

Abstract: This study was undertaken with the aim of investigating the effect of Cd 2+ and Ni 2+ containing solutions on selected physiological parameters (metal uptake, chlorophyll a fluorescence, assimilation pigment composition, thiobarbituric acid-reactive substance production, and ergosterol content) in the lichens Peltigera rufescens and Cladina arbuscula subsp. mitis growing on historic copper mine-spoil heaps at Ľubietová-Podlipa, Slovakia. Physiological measurements did not confirm significantly higher sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
6
15
0
Order By: Relevance
“…On the other hand, wear of tires, brakes, engine, and vehicle components is a well known source of Cd and Sb atmospheric pollution (Cadle et al 1997, Beckerman et al 2008). However, it should be considered that intracellular concentrations of Cd and Sb measured in the present study (range of seasonal average: Cd=0.03-0.08 µg g -1 dw, Sb=0.22-0.46 µg g -1 dw) were low and in line with intracellular values reported for lichens from unpolluted areas (Bačkor et al 2010, Paoli et al 2013b. Nevertheless, assuming Sb as a main tracer of traffic emissions, positive correlations emerged between Sb and Ba (r=0.52, p<0.05), Cr (r=0.65, p<0.001), Cu (r=0.66, p<0.001), Fe (r=0.37, p<0.05) and Zn (r=0.70, p<0.001), suggesting also that the intracellular content of these elements was partially associated with vehicular traffic.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, wear of tires, brakes, engine, and vehicle components is a well known source of Cd and Sb atmospheric pollution (Cadle et al 1997, Beckerman et al 2008). However, it should be considered that intracellular concentrations of Cd and Sb measured in the present study (range of seasonal average: Cd=0.03-0.08 µg g -1 dw, Sb=0.22-0.46 µg g -1 dw) were low and in line with intracellular values reported for lichens from unpolluted areas (Bačkor et al 2010, Paoli et al 2013b. Nevertheless, assuming Sb as a main tracer of traffic emissions, positive correlations emerged between Sb and Ba (r=0.52, p<0.05), Cr (r=0.65, p<0.001), Cu (r=0.66, p<0.001), Fe (r=0.37, p<0.05) and Zn (r=0.70, p<0.001), suggesting also that the intracellular content of these elements was partially associated with vehicular traffic.…”
Section: Discussionsupporting
confidence: 89%
“…However, a decrease was observed only eight days after the exposure suggesting the relative resistance of the lichen photobiont to short-term exposure to high Cd concentration. Bačkor et al (2010) also reported relatively low toxicity of Cd, compared to other metals, e.g. Cu in lichens Peltigera rufescens and Cladina arbuscula 24 h after the exposure.…”
Section: Discussionmentioning
confidence: 82%
“…In the last 20 years, chlorophyll fl uorescence measurements were successfully employed in various lichen studies investigating heavy metal pollution (Bačkor et al 2010, Karakoti et al 2014, Paoli et al 2015a). The maximum quantum yield of PSII (F v /F m ), besides being an important indicator of photosynthetic effi ciency, can indicate the vitality of a lichen photobiont (Paoli et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features of lichens, combined with their extraordinary capability to grow in a large geographical range and accumulate mineral elements far above their needs, rank them among the best bioindicators (Garty et al, 2003). The ability of lichens to tolerate and even bioaccumulate heavy metals such as As, Pb or Cd, has been extensively studied (Bajpai and Upreti, 2012;State et al, 2012;Ba ckor et al, 2011;Pawlik-Skowronska and Ba ckor, 2011;Ba ckor et al, 2010) as well as the noxious effects of inorganic pollutants such as O 3 , SO 2 or NO x (Riddell et al, 2012;Hauck et al, 2008;Tretiach et al, 2007;Hauck, 2010). However, the toxic effects of volatile organic pollutants (VOPs) on lichens have not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%